English speaking anxiety among English-major tertiary students in Ghana - Daniel Arkoh Fenyi; Angel Edward Kongo; Michael Owusu Tabiri; Ivy Jones-Mensah (International Journal of Evaluation and Research in Education (IJERE), 2023)
The study explored the English-speaking anxiety of trainee teachers in the colleges of education in Ghana. It aimed at unravelling the causes of the speaking anxiety in the learners and proffering strategies to mitigate the causes of the speaking anxiety. For that purpose, qualitative data were collected from 30 English-major students who attend a college of education in the Western North region of Ghana using semi-structured interviews as the data collection instrument. The data were analyzed using inductive coding data analysis procedures and techniques, where the dominant patterns and themes emerging from the data were grouped and examined. The results showed that the major causes of speaking anxiety are inferiority complex, fear of committing mistakes, spontaneity and the lack of preparation, fear of negative evaluation from tutors and peers, limited knowledge and vocabulary in the language and self-criticism. The participants also indicated the strategies that can curb the problem, including creating a learner-friendly and less formal classroom environment, peer assessment, encouraging the use of more speaking activities in the classroom, positive evaluative feedback and resignation and avoidance. In line with these findings, the study recommended that future research could employ a quantitative approach to produce a more generalizable outcome.